Pengaruh Daya Tarik Wisata, Kepekaan Lingkungan, dan Kepuasaan Layanan Terhadap Keterikatan Tempat Serta Implikasinya Pada Sikap Berprilaku Bertanggung Jawab Lingkungan - Putra, Wahyu Heryanto; Saputra, Fachri Eka (Master of Management Diponegoro University, 2020)
This study aims to examine the effect of destination attractiveness, environmental sensitivity, satisfaction with interpretive services, toward place attachment. This study also aims to identify the effect of place attachment to environmental responsible behaviour. This study was using questionnaire as data collection method. The total sample of this study was 400 respondents. However, the number of questionnaires that can be processed was 398. The data were proccesed using PLS SEM (Partial Least Square). The result were obtained in this study: (1) destination attractiveness influences positive significant place attachment (2) environmental sensitivity influences positive significant place attachment (3) satisfaction with interpretive services influences positive significant place attachment (4) place attachment influences positive significant environmental responsible behaviour (5) destination attractiveness influences positive significant environmental responsible behaviour (6) environmental sensitivity influences positive significant environmental responsible behaviour (7) satisfaction with interpretive services influences positive significant environmental responsible behaviour. This research contributes to the literature on tourism marketing.